1984
DOI: 10.1136/gut.25.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Motor activity of the distal oesophagus and gastrooesophageal reflux.

Abstract: SUMMARY The relationship between intraoesophageal pH value and motor activity of the lower oesophageal body ard sphincter was in-vvstigated by simultaneous evaluation of intraluminal pressure and pH in 13 patients complaining of heartburn and regurgitation. One hundred and thirty one episodes of gastro-oesophageal reflux were recorded. One hundred and eighteen (90.1%) were preceded by a swallow (one to 12 seconds), 13 reflux episodes (9.9%) were not preceded by a swallow. Gastro-oesophageal refluxes preceded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Our findings are similar to those described by other authors [7,[9][10][11][12][13][14][15], and suggest that the minimal or slight inflammatory changes in oesophageal mucosa cause a state of irritability with a tendency towards spastic con tractions of the oesophageal musculature, whereas severe inflammation leads to a decrease and, in some cases, a total loss of muscle contractability. These alterations lead to a poor clearance of refluxed material, which increases the duration of acid exposure of oesophageal mucosa, as was confirmed in our pH-metric study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings are similar to those described by other authors [7,[9][10][11][12][13][14][15], and suggest that the minimal or slight inflammatory changes in oesophageal mucosa cause a state of irritability with a tendency towards spastic con tractions of the oesophageal musculature, whereas severe inflammation leads to a decrease and, in some cases, a total loss of muscle contractability. These alterations lead to a poor clearance of refluxed material, which increases the duration of acid exposure of oesophageal mucosa, as was confirmed in our pH-metric study.…”
Section: Discussionsupporting
confidence: 81%
“…However, there is less information available on the role played by oesophageal motor alterations in the pathogenesis of this disease and even controversy on the subject. Thus, while some authors [7,[9][10][11][12][13][14][15] claim that peristaltic dysfunction is secondary to gastro-oesophageal reflux, others [8,[16][17][18][19] believe that it is a primary motor disorder forming part of a multifactorial aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…Complete sphincter relaxation usually follows a swallow, and since these events occur frequently in the awake state, it has been suggested that up to 40% of reflux episodes are associated with swallowing-induced sphincter relaxations. On the other hand, considerably lower figures for these associations have been presented by investigators using reliable recording techniques (2)(3)(4)(5)(6)(7)(8). It appears that swallow-induced reflux episodes are more likely to be associated with defective oesophageal peristalsis ( 2 , S ) and are common in patients with hiatus hernia ( 9 , 10).…”
mentioning
confidence: 87%
“…A separate analysis was performed for the number of complete peristaltic contraction waves needed to increase esophageal pH above 5. For this analysis, swallows with failed peristalsis, low-amplitude contractions, and simultaneous contractions were not counted since these types of contractions insuf -ciently clear re ux (16,17,(28)(29)(30)(31). A failed peristalsis was de ned as no contraction response in the esophagus after a pharyngeal swallow signal or a disappearance of the peristaltic sequence in the distal part of the esophagus.…”
Section: Acid Clearance Testmentioning
confidence: 99%